Production of hydrogen-rich syngas from biogas reforming with partial oxidation using a multi-stage AC gliding arc system - Nongnuch Rueangjitt (2018)
The aim of this research work was to evaluate the possibility of upgrading the simulated biogas (70 % CH4and 30 % CO2) for hydrogen-rich syngas production using a multi-stage AC gliding arc system. The results showed that increasing stage number of plasma reactors, applied voltage and electrode gap distance enhanced both CH4and CO2conversions, in contrast with the increases in feed flow rate and input frequency. The gaseous products were mainly H2and CO, with small amounts of C2H2, C2H4and C2H6. The optimum conditions for hydrogen-rich syngas production using the four-stage AC gliding arc system were a feed flow rate of 150 cm3/min, an input frequency of 300 Hz, an applied voltage of 17 kV and an electrode gap distance of 6 mm. At the minimum power consumption (3.3 × 10-18W s/molecule of biogas converted and 2.8 × 10-18W s/molecule of syngas produced), CH4and CO2conversions were 21.5 and 5.7 %, respectively, H2and CO selectivities were 57.1 and 14.9 %, respectively, and H2/CO (hydrogen-rich syngas) was 6.9. The combination of the plasma reforming and partial oxidation provided remarkable improvements to the overall process performance, especially in terms of reducing both the power consumption and the carbon formation on the electrode surface but the produced syngas had a much lower H2/CO ratio, depending on the oxygen/methane feed molar ratio. The best feed molar ratio of O2-to-CH4ratio was found to be 0.3/1, providing the CH4conversion of 81.4 %, CO2conversion of 49.3 %, O2conversion of 92.4 %, H2selectivity of 49.5 %, CO selectivity of 49.96 %, and H2/CO of 1.6. © Springer Science+Business Media, LLC 2011.